An analysis of security threats to mobile IPv6. (29th September 2008) - Durr, Michael; Hunt, Ray
In parallel with the design of IPv6, several protocol extensions for mobility support of IPv6 nodes have been proposed and these continue to evolve. However, a variety of security threats arise and these have to be taken in to account in the design of such protocol extensions. This paper provides a short introduction to Mobile IPv6 and presents a comprehensive overview of security issues that have to be taken into account when introducing mobility support. Furthermore, security solutions included in the protocol design are addressed and a detailed explanation on how these solutions can assist in preventing security attacks is provided.